1973
DOI: 10.1038/bjc.1973.68
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Urea-extracted Proteins of Mouse Epidermis and Squamous cell Carcinomata Determined by Fluorescence Microscopy

Abstract: Summary.-Fluorescence microscopy was used to demonstrate differences in the urea-extractable antigens of mouse epidermis and squamous cell carcinoma. When serum-and normal tissue sediment-absorbed antisera prepared against mouse epidermal urea-extracted proteins were further absorbed with carcinoma urea antigens, antisera specific for epidermis resulted. When antisera raised against the urea-extractable proteins of mouse squamous cell carcinomata were serumand normal tissue sediment-absorbed and then further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1974
1974
1981
1981

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…On the other hand, when a mixture of IgG preparations or antisera raised against the papilloma and carcinoma urea proteins reacted with the gel or supernatant fractions of these tissues, precipitin bands of identity resulted. Thus these immunodiffusion results on the gel and supernatant fractions of the urea proteins of epidermis and related tissues are in agreement with previous studies on antigenic differences between the urea proteins of epidermis and papilloma orcarcinoma[l, 3,7]. The urea proteins of papilloma and carcinoma appear to be similar as judged from the immunodiffusion ex periments given above and as is suggested by the amino acid composition of the urea proteins (table III).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…On the other hand, when a mixture of IgG preparations or antisera raised against the papilloma and carcinoma urea proteins reacted with the gel or supernatant fractions of these tissues, precipitin bands of identity resulted. Thus these immunodiffusion results on the gel and supernatant fractions of the urea proteins of epidermis and related tissues are in agreement with previous studies on antigenic differences between the urea proteins of epidermis and papilloma orcarcinoma[l, 3,7]. The urea proteins of papilloma and carcinoma appear to be similar as judged from the immunodiffusion ex periments given above and as is suggested by the amino acid composition of the urea proteins (table III).…”
Section: Resultssupporting
confidence: 92%
“…Recent studies employing immunodiffusion in agar suggested that the urea proteins of normal human epidermis and squamous-cell carcinoma were nonidentical [3]. These differences suggest the possibility of developing fluorescent labelled antisera specific for squamous-cell carcinoma and their detection in specific staining of tissue sections by fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations